Developing Seventh Grade Students’ Systems Thinking Skills in the Context of the Human Circulatory System - Raved, Lena; Yarden, Anat (Frontiers in Public Health, 2014)
Developing systems thinking skills in school can provide useful tools to deal with a vast amount of medical and health information that may help learners in decision making in their future lives as citizen. Thus, there is a need to develop effective tools that will allow learners to analyze biological systems and organize their knowledge. Here we examine junior high school students' systems thinking skills in the context of the human circulatory system. A model was formulated for developing teaching and learning materials and for characterizing students' systems thinking skills. Specifically we asked whether 7th grade students, who studied about the human circulatory system, acquired systems thinking skills and what are the characteristics of those skills? Concept maps were used to characterize students' systems thinking components and examine possible changes in the students' knowledge structure. These maps were composed by the students before and following the learning process. The study findings indicate a significant improvement in the students' ability to recognize the system components and the processes that occur within the system, as well as the relationships between different levels of organization of the system, following the learning process. Thus, following learning students were able to organize the systems’ components and its processes within a framework of relationships, namely the students' systems thinking skills were improved in the course of learning using the teaching and learning materials.